Hemodynamic effects of magnesium sulfate administration during anesthetic induction for laryngoscopy and orotracheal intubation: A randomized clinical trial (Research, Society and Development, 2024)
The hemodynamic response to laryngoscopy and orotracheal intubation stimuli, particularly hypertension and tachycardia, is a common phenomenon, and controlling this undesired reflex is a crucial part of anesthetic management. In this context, the aim of this study was to analyze the hemodynamic effects of magnesium sulfate administration during anesthetic induction for laryngoscopy and orotracheal intubation. It is a randomized, controlled, single-blind, prospective, and unicentric clinical trial conducted at a university hospital in a capital city in the Northeast region. Forty patients scheduled for orotracheal intubation following general anesthesia induction were evaluated and divided into two groups: Group 1: 10% magnesium sulfate, and Group 2: 0.9% saline solution. Participants aged between 18 and 59 years, scheduled for elective surgeries under general anesthesia with orotracheal intubation, and classified as ASA I or II, were included. The study population included individuals predominantly aged 46-59 years (32.5%), female (67.5%), classified as ASA I (60%), and from Teresina (62.5%). Regarding the evaluated physiological parameters, individuals in Group 1 showed lower mean values compared to the total sample and Group 2. The results of this study suggest that the administration of 10% magnesium sulfate during laryngoscopy and orotracheal intubation may be a suitable alternative. Magnesium sulfate administration can be an effective and safe method, with no apparent hemodynamic changes.